Cu2+ removal from synthetic wastewater using amine-modified bentonites: Kinetics and thermodynamic study based on multilinear regression (MLR) modeling - Khandamov, Davron; Kurniawan, Tonni Agustiono; Bekmirzayev, Akbarbek; Eshmetov, Rasulbek; Nurullaev, Shavkat; Babakhanova, Zebo; Batool, Fatima; AbdulKareem-Alsultan, G. (Taiwan Institute of Chemical Engineers, 2024)
Background: Water pollution due to heavy metals such as Cu(II) has become a public concern in developing world. This article studies the adsorption of Cu2+ ions from aqueous solutions on aminated bentonites of the Kongyrtog mine (Uzbekistan). Method: Batch studies were carried out at Cu(II) concentration varying from 30-350 mg/L, pH 7.0, dose of adsorbents (1 g/L) and varying temperatures from 293 to 333 K. Multilinear regression (MLR) modeling was conducted to test the fitness of the model for Cu(II) adsorption by the adsorbents. (Significant findings) It was found that the maximum Langmuir adsorption capacities (qmax) were attained as follows: coarse-grained bentonite (KB): 3.728; hexamethylenediammonium bentonite (GDB): 4.490; ethylene diammonium bentonite (EDB): 5.986 mg/g. The adsorption of Cu2+ was predominantly rapid in the first 10 min of reaction. After 1 h, an adsorption equilibrium was achieved due to the saturated adsorption sites. The comparison of kinetic models was consistent with a pseudo-second order kinetic model for the reaction adsorption. According to the magnitude of Cu2+ adsorption, adsorbents were distributed as follows: EDB > GDB > KB based on adsorption capacity. EDB has the greatest adsorption capacity, as ethylene diammonium cations were located perpendicularly between the bentonite layers due to the large size of hexamethyl-enediammonium cations. Multilinear regression (MLR) model successfully correlated the independent variables of the Cu(II) adsorption with the removal efficiency of the EDB and GDB. This reveals the applicability of the model for Cu(II) adsorption by the adsorbents under optimizing conditions. Conclusion: Overall, the adsorption of Cu2+ on aminated adsorbents depends on the initial concentration of metal ions, solution medium, reaction time, and temperature. © 2024 Taiwan Institute of Chemical Engineers